CHILDREN AND PRAYER: a shared pilgrimage - CLOYD, Shannon, Betty (Great Britain Patternoster-Publishing, 1997)
Children and prayer offers practical guidelines for teaching children about prayer and helping them to grow in their own unique prayer life with god.